KONSEP PENDIDIKAN ISLAM PERSPEKTIF AL-GHAZALI - Alwan Suban (Idaarah: Jurnal Manajemen Pendidikan, 2020)
The purpose of this article is to analyze the conception of Islamic Education from the perfectives of Al-Ghazali. This article used library research to review Al-Ghazali’s thoughts and conceptions on Islamic Education. The results shows that Al-Ghazali had a thorough understanding of Islamic Education. This paper also reveals his thoughts and understanding on education management, managing learners, and managing curriculum. This paper concludes that education according to Al-Ghazali is the process of humanizing humanity until the end of their lives towards a self-approach to God so that they become perfect human beings. Al-Ghazali describes the things that must be fulfilled by students in the learning process: learning is a soul process, requires concentration, must be based on the attitude of tawadhu'. Regarding a curriculum, he paid special attention to the religious and ethical sciences and was based on two tendencies: religious tendencies and Sufism; and pragmatic tendencies.